Optimal management of early surgery of chronic pancreatitis - Mikheiev, Yu. O.; Yareshko, V. H.; Skrypko, V.; Babii, O.; Shpylenko, O.; Міхеєв, Юрій Олександрович; Ярешко, Володимир Григорович (My University, 2021)
The present research aims to investigate whether there are advantages of early Surgery treatment or not, especially for pain relief. Retrospective analysis of data of 147 patients from 2001 to 2020 was conducted, which underwent Surgery treatment of chronic pancreatitis. Patients who had been suffering from chronic pancreatitis symptoms for 3 years or more were included in the control group (“late Surgery treatment”), and patients who had been noting symptoms of chronic pancreatitis less than 3 years were included in the study group (“early Surgery treatment”). All patients completed the EORTC QLQ-30, SF-36 questionnaires, as well as the questionnaire developed by the research authors, via telephone or mail or during the visit. According to all scales of the SF 36 questionnaire, except for “Physical functioning”, the group of “Early Surgery treatment” prevails over the group of “Late Surgery treatment”. The “Early Surgery treatment” group had the best average scores on all functional scales of the EORTC QLQ-30 questionnaire compared to the “Late Surgery treatment” group, except for the Cognitive Functioning scale. From the symptomatic scales, the “Early Surgery treatment” group had the best averages of Pain and Diarrhoea.
Keywords: chronic; duodenal obstruction; general health; pancreas; pancreaticoduodenectomy; pancreatitis; patients; steatorrhea